Fe2O3-CNT material loaded with ionic liquid and application of preparation method of Fe2O3-CNT material in electrocatalytic reduction of N2
By loading Fe2O3 on carbon nanotubes and combining with hydrophobic ionic liquids, Fe2O3-CNT-IL modified electrodes were prepared, which solved the problem of difficult cleavage of N≡N triple bonds in electrocatalytic nitrogen reduction reaction, achieving efficient nitrogen reduction, and improving ammonia production rate and Faraday efficiency.
Patent Information
- Application Number
- CN202510096721.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-03-21
AI Technical Summary
Electrocatalytic nitrogen reduction reaction (NRR) has the problem that N≡N three bonds are difficult to crack, resulting in low Faraday efficiency, high cost of precious metal catalyst materials, and low activity of non-precious metal catalyst materials.
The electrode is modified with Fe2O3-CNT-IL, and by loading Fe2O3 on carbon nanotubes and combining with hydrophobic ionic liquid, it provides a hydrophobic microenvironment, inhibits hydrogen evolution reaction, and improves the reduction efficiency of nitrogen.
It achieves efficient adsorption and activation of N2 under mild conditions, significantly improves NRR performance, improves ammonia production rate and Faraday efficiency, and has good material stability.
Smart Images

Figure CN119663365A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrochemical catalytic nitrogen reduction, and particularly relates to Fe 2 O 3 -Application of CNT-IL modified electrodes in electrocatalytic nitrogen reduction. Background Art
[0002] The electrocatalytic nitrogen reduction reaction (NRR) has attracted widespread attention from researchers due to its mild operating conditions, green environmental protection, and low energy consumption. However, the reaction has the problem that the N≡N triple bond is difficult to cleave. In addition, protons and electrons tend to undergo competitive hydrogen evolution reaction (HER) during the reaction, resulting in a very low Faraday efficiency (FE) of NRR. Although precious metal catalyst materials exhibit good NRR activity, their scarcity and high cost limit their possible applications; and non-precious metal catalyst materials (such as iron-based materials) have relatively low catalytic activity. The development of new NRR catalyst materials with high activity and selectivity has become a hot topic in this field.
[0003] As an ideal low-dimensional quantum material, carbon nanotubes have the advantages of low thermal conductivity, high electrical conductivity and large specific surface area. As a green solvent, ionic liquids have the advantages of good electrical conductivity, low volatility, and a wider electrochemical stable potential window than other electrolyte aqueous solutions. This patent intends to use iron-based catalysts with good catalytic properties, load them on carbon nanotubes to increase their conductivity, and react with hydrophobic ionic liquids. Ionic liquids can provide a hydrophobic microenvironment, inhibit hydrogen evolution reaction, and convert N 2 It is enriched on the electrode surface and fully contacts with the catalyst, thus improving the nitrogen reduction efficiency. Summary of the invention
[0004] The present invention aims to provide a Fe-based electrocatalytic nitrogen reduction system with high catalytic efficiency. 2 O 3 -CNT-IL modified electrode. The modified electrode shows excellent electrocatalytic activity for electrocatalytic nitrogen reduction, and the obtained Faradaic efficiency and ammonia production rate are both high. The technical solution adopted by the present invention is: a Fe-based ionic liquid 2 O 3 -CNT material, the preparation method comprises the following steps:
[0005] 1) Add FeNO to ethanol 3 9H 2 O and carbon nanotubes, and heating until the ethanol is completely volatilized;
[0006] 2) Place the sample in a porcelain boat for calcination. After the reaction is completed, cool it to room temperature and collect the sample for later use;
[0007] 3) Fe2 O 3 -CNT and IL were added to isopropanol and stirred at room temperature for 3 h, and then the solvent was removed by rotary evaporation at 40 °C to obtain a black solid Fe 2 O 3 -CNT-IL.
[0008] The above-mentioned Fe loaded with ionic liquid 2 O 3 -CNT material, in step 1), FeNO 3 9H 2 The mass ratio of O: carbon nanotubes is 1:1.
[0009] The above-mentioned Fe loaded with ionic liquid 2 O 3 -CNT material, in step 1), the heating temperature is 70°C.
[0010] The above-mentioned Fe loaded with ionic liquid 2 O 3 -CNT material, in step 2), the heating rate of calcination is 5°C / min, and the calcination is heated at 300°C for 5h.
[0011] The above-mentioned Fe loaded with ionic liquid 2 O 3 -CNT material, in step 3), the ionic liquid IL is 1-butyl 3-methylimidazolium hexafluorophosphate.
[0012] The above-mentioned Fe loaded with ionic liquid 2 O 3 -CNT material, in step 3), by mass ratio, Fe 2 O 3 - CNT: ionic liquid IL = 4:1.
[0013] A Fe 2 O 3 -CNT-IL modified electrode, the above Fe 2 O 3 -CNT-IL was coated on the surface of hydrophobic carbon cloth and placed at room temperature for 10 min to allow Fe 2 O 3 -CNT-IL and the hydrophobic carbon cloth surface are fully combined to produce Fe 2 O 3 -CNT-IL modified electrode.
[0014] The modified electrode mentioned above was used for electrocatalytic N 2 Converted to NH 3 The application is characterized in that the method is as follows: using the Fe as claimed in claim 72 O 3 -CNT-IL modified electrode was used as working electrode, Ag / AgC1 electrode as reference electrode, platinum sheet as counter electrode, 0.1M Na 2 SO 4 As electrolyte, 0.01MH 2 SO 4 The tail gas absorption liquid was used, nitrogen was introduced into the system, and the electrocatalytic N 2 Converted to NH 3 .
[0015] In the above application, the linear voltammetric scanning method has a scanning rate of 10 mV·s -1 .
[0016] In the above application, in the chronoamperometry, the electrolysis time is 7200 s.
[0017] The beneficial effects of the present invention are:
[0018] 1. Fe prepared by the present invention 2 O 3 -CNT-IL modified electrode, adsorbing and activating N under mild conditions 2 and promote N 2 Converted to NH 3 .Fe 2 O 3 -CNT-IL makes full use of the stable morphology of solids and the loading capacity of functional groups, while taking advantage of the liquid material enrichment and rapid mass transfer characteristics, achieving efficient synergistic expression of enrichment, catalysis and other functions. This synergistic effect significantly improves the NRR performance, provides novel ideas and methods for the research in the field of electrocatalytic nitrogen reduction, and helps promote further development in this field.
[0019] 2. The present invention controls the technical parameters in the catalytic process and reasonably matches the raw materials of the electrode materials, thereby improving the efficiency of electrochemical electrocatalytic nitrogen reduction, and improving the ammonia production rate and Faraday efficiency. 2 O 3 -CNT-IL modified electrode produces ammonia at a rate of 14.51 μg·h at an applied voltage of -0.5 V (vs. RHE) during the electrocatalytic nitrogen reduction process. -1 mg cat -1 , the Faraday efficiency is 24.82%. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is Fe 2 O 3 -CNT、Fe 2O 3 -XRD pattern of CNT-IL.
[0021] Figure 2A It is Fe 2 O 3 -SEM images of CNT and Figure 2B It is Fe 2 O 3 -SEM image of CNT-IL.
[0022] Figure 3 It is Fe 2 O 3 -CNT mapping diagram.
[0023] Figure 4 It is Fe 2 O 3 -Mapping diagram of CNT-IL.
[0024] Figure 5A The UV-visible absorption spectrum curve of different ammonium chloride solutions with known concentrations was tested by indigo blue colorimetry. The absorbance at 655 nm corresponds to NH 4 + concentration.
[0025] Figure 5B is the ammonia calibration curve used to calculate the NH 4 + The concentration of ions.
[0026] Fig. 6A The Watt-Chrisp method is used to test the UV-visible absorption spectrum curve of different hydrazine hydrate solutions with known concentrations. The absorbance at 455nm corresponds to the concentration of hydrazine hydrate.
[0027] Figure 6B The hydrazine calibration curve is used to calculate the concentration of hydrazine hydrate in the electrolyte.
[0028] Fig. 7A It is Fe 2 O 3 -CNT modified electrode in Ar and N 2 LSV plot under atmosphere.
[0029] Figure 7B It is Fe 2 O 3 -IT diagrams of electrocatalytic nitrogen reduction of CNT-modified electrodes at different potentials for 7200 s.
[0030] Figure 7C It is Fe 2 O 3UV-Vis absorption spectra of the electrolyte after color development using indigo method after the NRR reaction of the -CNT modified electrode for 7200 s at different potentials.
[0031] Fig.7D is Fe 2 O 3 NH production rate and Faraday efficiency diagrams of the -CNT modified electrode at different potentials. 3
[0032] Fig. 8A is Fe 2 O 3 LSV diagrams of the -CNT-IL modified electrode in Ar and N atmospheres. 2
[0033] Figure 8B is Fe 2 O 3 I-T diagrams of the -CNT-IL modified electrode for electrocatalytic nitrogen reduction at different potentials for 7200 s.
[0034] Figure 8C is Fe 2 O 3 UV-Vis absorption spectra of the electrolyte after color development using indigo method after the NRR reaction of the -CNT-IL modified electrode for 7200 s at different potentials.
[0035] Fig.8D is Fe 2 O 3 NH production rate and Faraday efficiency diagrams of the -CNT-IL modified electrode at different potentials. 3
[0036] Fig. 9 Diagram of the influence of different ionic liquid contents on electrocatalytic nitrogen reduction.
[0037] Fig.10 Diagram of excluding the influence of accidental factors on the experiment.
[0038] Fig.11 Diagram of stability efficiency and yield of 5 tests.
[0039] Fig.12 is the Mapping diagram of Fe 2 O 3 -CNT-IL after 5 electrolyses. Specific implementation method
[0040] Example 1 Fe 2 O 3 -CNT-IL modified electrode
[0041] (I) The preparation method is as follows
[0042] 1)Fe 2 O 3 Preparation of -CNT-IL
[0043] 1.1) Add 50 mL of ethanol to the three-necked flask and add an equal amount of FeNO 3 9H 2 O and carbon nanotubes were heated in an oil bath at 70 °C until the ethanol was completely evaporated;
[0044] 1.2) Remove the sample and place it in a porcelain boat, put it in a muffle furnace, and heat it at 300℃ for 5h. After the reaction is completed, cool it to room temperature and collect the sample for later use;
[0045] 1.3) 100 mg Fe 2 O 3 -CNTs and 25mg[BMIM]PF 6 The mixture was added with 1% ethyl acetate (25 wt.%) into isopropanol and stirred at room temperature for 3 h. The solvent was then removed by a rotary evaporator at 40°C to obtain a black solid for standby use.
[0046] 2) Electrode pretreatment
[0047] The hydrophobic carbon cloth was cut into a size of 1 cm × 1.5 cm.
[0048] 4)Fe 2 O 3 - Preparation of CNT-IL modified electrodes
[0049] The Fe obtained in step 2) 2 O 3 -CNT-IL was coated on the surface of hydrophobic carbon cloth and placed at room temperature for 10 min to allow Fe 2 O 3 -CNT-IL and carbon cloth surface are fully combined to produce Fe 2 O 3 -CNT-IL modified electrode.
[0050] (II) Testing
[0051] Figure 1 It is Fe 2 O 3 -CNT and Fe 2 O 3 -XRD pattern of CNT-IL. Figure 1 As shown, 33.1°, 35.6° and 54.0° correspond to Fe 2 O 3 The (104), (110), and (116) crystal planes of the FeO2O3 and FeO2O3 ...2 O 3 -CNT. After adding the ionic liquid, it was found that the peak position did not change, only the peak intensity changed, indicating that the addition of the ionic liquid did not change the material lattice.
[0052] Figure 2 shows Fe 2 O 3 -SEM image of CNT (A) and Fe 2 O 3 -SEM image of CNT-IL (B), it can be seen that the material is composed of tubular materials and spherical materials. The morphology of the material has not changed significantly after the addition of ionic liquid. The material is more compact and is conducive to the adsorption of nitrogen and the catalytic reaction.
[0053] Figure 3 Fe 2 O 3 -CNT Mapping diagram. According to the detailed data of the map, we can clearly see that the elements Fe, O, and C are evenly distributed on the surface of the material.
[0054] Figure 4 Fe 2 O 3 -Mapping diagram of CNT-IL. According to the detailed data of the map, we can clearly see that the elements Fe, O, C, P, F, and N are evenly distributed on the surface of the material.
[0055] Fig.12 Fe after 5 electrolysis 2 O 3 -Mapping diagram of CNT-IL. According to the detailed data of the map, we can still clearly see that the elements Fe, O, C, P, F, and N are evenly distributed on the surface of the material, indicating that the material has good stability.
[0056] Example 2Fe 2 O 3 -CNT-IL modified electrode for electrocatalytic N 2 Restoring Applications
[0057] Electrolysis product test: Ammonia content was tested using the indophenol blue method; hydrazine content was tested using the Watt-Chrisp method; the ammonia content was measured and then the Faraday efficiency and ammonia production rate were calculated.
[0058] The formula for calculating Faraday efficiency is FE% = (3F × n × V) × 100 / (17 × Q);
[0059] Where F is Faraday's constant and n is the NH 3 is the concentration of the electrolyte, Q is the charge, and V is the volume of the electrolyte.
[0060] The formula for calculating the ammonia production rate is v = (n × V) / (T × m);
[0061] Where n is the NH produced 3 The concentration of V is the volume of the electrolyte, T is the reaction time, and m is the mass of the catalyst.
[0062] The method is as follows: Fe 2 O 3 -CNT-IL modified electrode was used as working electrode, Ag / AgCl electrode as reference electrode, platinum sheet as counter electrode, and 0.1MH 2 SO 4 As electrolyte, the three-electrode system was placed in 0.1MH 2 SO 4 In the electrochemical determination, a CHI760e electrochemical workstation was used, and the linear voltammetric scanning method was used to determine whether the system could undergo nitrogen reduction and the voltage range in which nitrogen reduction occurred. The scanning rate was 10 mV·s -1 , using the chronoamperometric method to electrolyze nitrogen to convert it into ammonia. Before the electrochemical test, pass N 2 The gas was stirred for 30 minutes to ensure that the electrolyte was saturated with the corresponding gas. The solution after electrolysis was then measured by ultraviolet light, and the solubility of ammonia was calculated based on the measured standard curve, thereby calculating the ammonia production rate and Faraday efficiency. The potential was converted to the potential based on the reversible hydrogen electrode standard, and according to the Nernst equation E RHE =E Ag / AgCl +0.059pH+0.197V.
[0063] The working electrodes are selected as follows:
[0064] 1) Hydrophobic carbon cloth is the working electrode, marked as CC,
[0065] 2)Fe 2 O 3 -CNT-IL / CC, Fe 2 O 3 -CNT / CC,
[0066] 3)Fe 2 O 3 -CNT-IL modified electrode: Fe 2 O 3 -CNT-IL is uniformly coated on the carbon cloth and is recorded as Fe 2 O 3 -CNT-IL / CC, naturally dried and used as working electrode.
[0067] (I) Fe 2 O 3 -CNT-IL electrocatalytic nitrogen reduction
[0068] Before the electrocatalytic nitrogen reduction, the ammonia standard curve of the ammonia standard solution was first determined using the indophenol blue method, and the determination result is shown in Figure 5. The Watt-Chrisp method was also used to determine the standard curve of the possible byproduct hydrazine, and the determination result is shown in Figure 6.
[0069] Take 60mL of 0.1M Na 2 SO 4 The solution was placed in the two chambers of the H-type electrolytic cell. A three-electrode system was used, with the Ag / AgCl electrode as the reference electrode, the platinum sheet as the counter electrode, and the working electrodes as Fe 2 O 3 -CNT-IL / CC, Fe 2 O 3 -CNT- / CC, N was passed through before electrochemical testing 2 The gas was stirred for 30 minutes to ensure the saturation of the corresponding gas. The electrochemical determination was carried out using a CHI760e electrochemical workstation and chronoamperometric electrolysis for 7200 seconds. The test results are shown in Figures 7 and Fig. 9 shown.
[0070] Figure 7 is Fe 2 O 3 -CNT(A) modified electrode in Ar and N 2 LSV diagram under atmosphere. It can be seen from the figure that Fe 2 O 3 -CNT modified electrodes can undergo electrocatalytic nitrogen reduction reaction between -0.8 and -0.2 V (vs. RHE). Figure 7B It is Fe 2 O 3 -IT diagrams of electrocatalytic nitrogen reduction at CNT-modified electrodes for 7200 s at different potentials. Figure 7C It is Fe 2 O 3 -CNT modified electrode NRR reaction at different potentials for 7200s after the electrolyte was developed using the indigo method. Its Faraday efficiency and ammonia production rate were calculated according to the formula. The results are as follows Fig.7D According to the results, Fe 2 O 3 The ammonia yield and Faraday efficiency of the CNT modified electrode reached their maximum values at -0.50 V (vs. RHE), which were 9.46 μg·h -1 mg cat -1 , 18.07%.
[0071] Figure 8 is Fe 2 O 3 -CNT-IL(B) modified electrode in Ar and N2 LSV diagram under atmosphere. It can be seen from the figure that Fe 2 O 3 -CNT-IL modified electrode can undergo electrocatalytic nitrogen reduction reaction between -0.8 and -0.2 V (vs. RHE). Figure 8B It is Fe 2 O 3 -IT diagrams of electrocatalytic nitrogen reduction at CNT-IL modified electrode for 7200 s at different potentials. Figure 8C It is Fe 2 O 3 -CNT-IL, modified electrode NRR reaction at different potentials for 7200s after the electrolyte was developed using the indigo method UV-visible absorption spectra. The Faraday efficiency and ammonia production rate were calculated according to the formula. The results are as follows Fig.8D According to the results, Fe 2 O 3 The ammonia yield and Faraday efficiency of the CNT-IL modified electrode reached their maximum values at -0.50 V (vs. RHE), which were 24.82 μg·h -1 mg cat -1 , 14.51%.
[0072] (2) Fe 2 O 3 -CNT-IL, Fe 2 O 3 -CNT modified CC at -0.5V (vs.RHE) 2 Saturated 0.1M Na 2 SO 4 Electrocatalytic ammonia synthesis performance
[0073] A three-electrode system was used, with Ag / AgCl electrode as the reference electrode, platinum sheet as the counter electrode, and Fe 2 O 3 -CNT-IL, Fe 2 O 3 -CNT modified CC, electrochemical determination was performed using a CHI760e electrochemical workstation at -0.5 V (vs. RHE) under N 2 Saturated 0.1M Na 2 SO 4 Electrocatalytic synthesis of ammonia.
[0074] Different modified electrodes at -0.5 V (vs. RHE) in N 2 Saturated 0.1M Na 2 SO 4After 7200s of NRR reaction, the electrolyte was developed using the indigo method and then subjected to UV-visible absorption spectroscopy to measure the ammonia concentration, such as Fig.10 , and then calculate the Faradaic efficiency and ammonia production rate of different electrodes. When Ar, CC, and OCP are used to modify the electrodes, the ammonia production rate and Faradaic efficiency are extremely low and almost negligible. 2 O 3 The excellent electrocatalytic nitrogen reduction performance of CNT-IL is mainly attributed to its 2 The enrichment effect of the ionic liquid and the efficient charge transfer microenvironment provided by the internal ionic liquid. This microenvironment has abundant active sites, which makes the catalyst show high reactivity and selectivity in the reaction and has good cycle performance.
[0075] (III) Fe 2 O 3 -CNT-IL modified electrode electrocatalytic nitrogen reduction stability
[0076] Make Fe 2 O 3 -CNT-IL modified electrode at -0.5 V (vs. RHE) 2 Saturated 0.1M Na 2 SO 4 The electrocatalytic synthesis of ammonia was cycled five times to determine its stability. The test results are as follows Fig.11 The results show that Fe 2 O 3 The Faradaic efficiencies of the five cycles of -CNT-IL were 27.01%, 26.94%, 26.87%, 25.75%, and 26.63%, respectively, and the ammonia production rates of the five cycles were 23.84, 23.72, 23.66, 23.58, and 23.41 μg·h -1 mg cat -1 The ammonia production rate and Faraday efficiency did not change much, and the ammonia yield and FE still maintained 92.9% and 94.2% of the original values. This result shows that Fe 2 O 3 -CNT-ILs have good NRR stability and durability.
Claims
1. An Fe2O3-CNT material loaded with ionic liquid, characterized in that: The preparation method comprises the following steps: 1) Add FeNO3·9H2O and carbon nanotubes to ethanol and heat until the ethanol is completely evaporated; 2) Remove the sample and place it in a porcelain boat for calcination. After the reaction is completed, cool it to room temperature and collect the sample for later use; 3) Fe2O3-CNT and ionic liquid IL were added to isopropanol and stirred at room temperature for 3 h, and then the solvent was removed by a rotary evaporator at 40 °C to obtain a black solid Fe2O3-CNT-IL.
2. The Fe2O3-CNT material loaded with ionic liquid according to claim 1, characterized in that: In step 1), the mass ratio of FeNO3·9H2O to carbon nanotubes is 1:
1.
3. The Fe2O3-CNT material loaded with ionic liquid according to claim 1, characterized in that: In step 1), the heating temperature is 70°C.
4. The Fe2O3-CNT material loaded with ionic liquid according to claim 1, characterized in that: In step 2), the heating rate of calcination is 5°C / min. The calcination is performed at 300°C for 5h.
5. The Fe2O3-CNT material loaded with ionic liquid according to claim 1, characterized in that: In step 3), the ionic liquid IL is 1-butyl 3-methylimidazolium hexafluorophosphate.
6. The Fe2O3-CNT material loaded with ionic liquid according to claim 1, characterized in that: In step 3), the mass ratio is Fe2O3-CNT: ionic liquid IL = 4:
1.
7. A Fe2O3-CNT-IL modified electrode, characterized in that: The Fe2O3-CNT-IL described in any one of claims 1 to 6 is coated on the surface of the hydrophobic carbon cloth and placed at room temperature for 10 minutes to allow the Fe2O3-CNT-IL and the hydrophobic carbon cloth surface to fully combine to obtain a Fe2O3-CNT-IL modified electrode.
8. Use of the modified electrode according to claim 7 in electrocatalytic conversion of N2 into NH3, characterized in that: The method is as follows: the Fe2O3-CNT-IL modified electrode described in claim 7 is used as the working electrode, the Ag / AgCl electrode is used as the reference electrode, the platinum sheet is used as the counter electrode, 0.1M Na2SO4 is used as the electrolyte, 0.01M H2SO4 is used as the tail gas absorption liquid, nitrogen is introduced into the system, and linear voltammetry and chronoamperometry are used to electrocatalyze the conversion of N2 into NH3.
9. The use according to claim 8, characterized in that: In the linear voltammetry method, the scanning rate is 10 mV·s -1 .
10. The use according to claim 8, characterized in that: In the chronoamperometry method, the electrolysis time is 7200 s.